Dutch Nationwide Implementation Program for familial hypercholesterolemia case finding in children: a cost-effectiveness and return on investment analysis. (3rd October 2022) - Ademi, Z; Norman, R; Sijbrands, E; Ference, B A; Watts, G F; Hutten, B; Wiegman, A
Abstract: Background: The Netherlands is one of the few countries in the world that actively screen for familial hypercholesterolemia (FH). Objectives: We investigated the return on investment (ROI) and cost-effectiveness of the Dutch nationwide implementation program for FH case-finding and preventive treatment in children compared to later detection and treatment from both a societal and healthcare perspective in the Netherlands. Methods: Cascade case finding and early preventive treatment were modelled to simulate the progression of disease and costs of ten-year-olds suspected of having heterozygous FH (HeFH) over a lifetime. The model consisted of three health states: alive without coronary heart disease (CHD), alive with CHD, and dead. The decision was to compare the nationwide implementation program for FH cascade case-finding in children and immediate treatment with statins compared to "usual care" later detection and treatment. The prevalence of HeFH in this target population was 51.2% as per the Dutch Health Program for FH case-finding, and the sensitivity and specificity of testing was 100%. Contemporary Mendelian Randomisation Analysis data was used to quantify the risk of a first coronary heart disease event as a function of age and total lifetime exposure to low-density-lipoprotein cholesterol. Costs and outcome were sourced from the Dutch data and other published sources. ROI for the Dutch nationwide implementation program for FH case-finding and cost-effectiveness analyses using incremental cost-effectiveness ratios (ICERs) (cost per quality-adjusted life years (QALYs) gained), compared with current usual care were the main outcomes of interest. All future benefits and costs were discounted annually by 1.5% and 4% respectively. Results: Over the lifetime horizon, the ROI for the Dutch nationwide implementation program for FH case-finding was €16.52 (i.e. every euro spent on the program resulted in a return of €16.52). From the societal perspective, the Dutch nationwide implementation program for FH case-finding and early treatment with statins was the dominant strategy (health improvement and cost saving) compared to usual care. From a healthcare perspective, the Dutch nationwide implementation program for FH case-finding and early treatment with statins would gain 2.64 QALYs per person, at an additional cost of €7, 178 (both discounted). These equated to an ICER of €2, 668 per QALY gained. Conclusions: From the societal perspective, the the Dutch nationwide implementation program for FH case-finding represented excellent value for investment for Netherlands, being not only health saving but also cost saving form a societal perspective and cost effective from a healthcare perspective. Funding Acknowledgement: Type of funding sources: None.